Online workshop on output sharing and feedback from demand partners - International Rice Research Institute (International Rice Research Institute, 2026)
On January 13, 2026, the International Rice Research Institute (IRRI) conducted an online workshop (Fig 1). A representative from Jeevika, a demand partner focused on women's livelihoods, participated in the workshop. Representatives from Bihar Agriculture University and IKSL were unable to attend due to scheduling conflicts. Several representatives from IRRI also participated.